(untitled) (Research, Society and Development, 2021)
Essential oils have often been used as an alternative tool for the control of larvae and mosquitoes of various genres. The genus Anopheles, known to be the transmitter of malaria, has been tested with the use of essential oils obtained from several plant species. These mosquitoes carry as parasites the protozoan of the genus Plasmodium, which is responsible for causing the disease. Due to the need to know more and more alternatives for the control of these vectors, the present study aimed to carry out a survey of the use of essential oils of different species to combat the malaria vector, that is, in mosquitoes of the genus Anopheles, acting directly on larvae of these mosquitoes. This survey was carried out using the Science Direct and Scielo database, selecting works from the years 2010 to 2020, thus analyzing their title and objective. In this work, the essential oils of 33 species of plants, belonging to 16 different families against mosquito larvae of this genus, were evaluated, and the effectiveness of the essential oil was evaluated from the value of LC50. Therefore, this article highlights the great relevance of the use and effectiveness of essential oils in the control of Anopheles mosquitoes.